Unidades proterozoicas da região do Alto Rio Pardo e da Serra do Espinhaço Central: considerações sobre sua estratigrafia e seus paleoambientes - Diego Ferreira Lima e Correa Pereira (2018)
The central portion of the Espinhaço Range and the Alto Rio Pardo region, in the vicinity of the border between the states of Minas Gerais and Bahia, harbor two important meta-volcano-sedimentary and meta-sedimentary sequences: the Espinhaço Supergroup and the Macaúbas Group. The results of geological mapping, petrographic characterization, geochronological and geochemical analyzes are presented and discussed in two scientific papers. The first paper is about the geology of the central portion of the Espinhaço Range, on the border between the states of Minas Gerais and Bahia, focused on the Espinhaço Supergroup, which is characterized in this area by an Inferior Unit, corresponding to the filling of a rift by sediments of alluvial and eolian environments associated to acid volcanism (dacitic/rhyodacitc, magnesian alkali-calcic) dated at 1766 ± 4 Ma. The entire Lower Unit is intruded by sills of basic magmatic rocks. The Middle Unit is characterized by metasedimentary rocks deposited mainly in eolian environment, locally presenting characteristic sedimentary facies of alluvial fan environment sedimentation. It is interpreted that the terrigenous and magmatic rocks associated to the Inferior Unit probably represent the initial stages of the breakdown of the São Francisco-Congo Paleocontinent in the Statherian Period. The Middle Unit was deposited after the cessation of volcanism in the region, but still presents evidences of tectonism in its basal portion. The top of that unit already represents the transitional phase of the rift. The second paper deals with the Rio Peixe Bravo Formation in the northwestern portion of the Araçuaí Orogen, in the western part of the Rio Pardo Salient. That formation was divided into two units in gradational contact: the Meta-arenitic Unit, which consists of a thick sedimentation of varied meta-sandstones (mainly) deposited in a coastal environment, and the Metapelitic Unit, which is represented by mica schists, staurolite-garnet-mica schists, kyanite-mica schists, graphite phyllites and, subordinately, micaceous sandstones, for which a sedimentation in a marine platform environment was interpreted. The general character of this sequence is transgressive retrogradational. The geochronology by the U-Pb method in detrital zircons provided a maximum sedimentation age of about 1.8 Ga, but the field data show its intimate relationship with the Macaúbas Group in the region.